Weighted gene co-expression network analysis identifies dysregulated B-cell receptor signaling pathway and novel genes in pulmonary arterial hypertension - Chen, Yuanrong; Wu, Chaoling; Wang, Xiaoping; Zhou, Xufeng; Kang, Kunpeng; Cao, Zuofeng; Yang, Yihong; Zhong, Yiming; Xiao, Genfa (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulmonary arterial hypertension (PAH) is a devastating cardio-pulmonary vascular disease in which chronic elevated pulmonary arterial pressures and pulmonary vascular remodeling lead to right ventricular failure and premature death. However, the exact molecular mechanism causing PAH remains unclear. Methods: RNA-sequencing was used to analyze the transcriptional profiling of controls and rats treated with monocrotaline (MCT) for a variety of weeks. Weighted gene co-expression network analysis (WGCNA) was employed to identify the key modules associated with the severity of PAH. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed to explore their potential biological function and pathway. The hub genes were validated by an independent dataset obtained from the Gene Expression Omnibus database. Results: A total of 26 modules were identified by WGCNA. Among them, the darkred and blue modules showed the strongest correlation with the severity of PAH and were recognized as the key modules. GO analysis of key modules showed that these genes were mainly enriched in terms related to inflammation and immunity, particularly B cell-mediated humoral immunity. KEGG pathway analysis showed the significant enrichment of B cell receptor signaling pathway in key modules. Pathway-based data integration and visualization revealed the dysregulation of B cell receptor signaling pathway in PAH. In addition, a series of humoral immune response-associated genes and 5 hub genes including BANK1, FOXF1, TLE1, CLEC4A1 and CLEC4A3 were identified. Conclusion: This study identified two key modules associated with the severity of PAH, and dysregulated B cell receptor signaling pathway as well as novel genes associated with humoral immune response in MCT-induced PAH, thus providing a novel perspective into the understanding of the molecular mechanism in PAH.